SISTEM PENENTUAN PENCERAMAH MASJID PARIPURNA KOTA PEKANBARU MENGGUNAKAN ALGORITMA PENGKLASTERAN K-MEANS - Silfia Silfia; Rahmad Kurniawan; Nazruddin Safaat Harahap; Elvia Budianita; Fadhilah Syafria; Iwan Iskandar (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2021)
There are 903 mosques in Pekanbaru City, Riau Province. In 2016, the Pekanbaru City Government formed a Paripurna Mosque program which the Pekanbaru Paripurna Mosque Management Agency manages. Each mosque holds religious activities which a preacher fills. The mosque has a regular schedule of lectures with a short transition period for each type of religious activity held. Based on observations, the mosque management did not get complete information regarding the profile of the preacher. Furthermore, many preachers have canceled lecture schedules due to distance issues and the suitability of the lecturer's profile with the congregations. Therefore, a recommendation system using the K-means algorithm is necessary based on coordinate points, location access, and appropriate types of religious activities for the Pekanbaru Paripurna Mosque. This study also employed one hot encoding technique for non-numeric data. Based on the experimental testing results on the five clusters, the silhouette coefficient value is 0.945. Based on the results, it can be concluded that the system for determining the preachers of the Pekanbaru City Paripurna Mosque has the potential to be used.